2012
DOI: 10.4187/respcare.01605
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane for Life-Threatening Bronchospasm: A 15-Year Single-Center Experience

Abstract: Introduction Children with severe bronchospasm requiring mechanical ventilation may become refractory to conventional therapy. In these critically ill patients, isoflurane is an inhaled anesthetic agent available in some centers to treat bronchospasm. We hypothesized that isoflurane is safe and would lead to improved gas exchange in children with life-threatening bronchospasm refractory to conventional therapy. Methods A retrospective review was conducted and included mechanically ventilated children treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…It is suggested that inhalational anesthetics can cause h y p o t e n s i o n a n d n e u r o c o g n i t ive i m p a i r m e n t . Hypotension can result through vasodilatory effects of inhalational anesthetics 3) . However, the hypotension observed on ICU admission was mitigated with sevo urane therapy in our patient, presumably because the vasodilation was resolved by the improved venous return associated with mitigation of auto-PEEP and dynamic hyperin ation 14) .…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that inhalational anesthetics can cause h y p o t e n s i o n a n d n e u r o c o g n i t ive i m p a i r m e n t . Hypotension can result through vasodilatory effects of inhalational anesthetics 3) . However, the hypotension observed on ICU admission was mitigated with sevo urane therapy in our patient, presumably because the vasodilation was resolved by the improved venous return associated with mitigation of auto-PEEP and dynamic hyperin ation 14) .…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective reviews demonstrate that the initiation of these gases is consistently associated with a decrease in P aCO 2 around 20 mm Hg and concomitant rise in pH of about 0.1 within a few hours of administration. 105,108,111,[113][114][115] The largest case series to date includes 31 children over a 15-y period, in which children received isoflurane for a mean duration of 55 h (range 1-181 h) and were invasively ventilated for a mean of 252 h (range 16 -1,444 h). The majority (77%) of these children developed hypotension requiring vasopressor support, but all survived without long-term sequelae.…”
Section: Inhaled Anestheticsmentioning
confidence: 99%
“…Inhalational agents such as isoflurane and sevoflurane are potent bronchodilators that have been used in children with near-fatal asthma. ( 92 , 93 ) Their use is limited by technical issues and safety concerns. Most ventilators used in the ICU do not have a scavenger system for proper disposal of inhaled anesthetics, and anesthesia machines commonly used in the operating room may not be sufficiently sophisticated to ventilate children with near-fatal asthma.…”
Section: Refractory Casesmentioning
confidence: 99%
“…Side effects include hypotension, arrhythmias, and movement disorders. ( 92 , 93 ) Inhaled anesthesia was reported in 3% of cases in the CPCCRN study, while ECLS was used in only 1%. ( 10 ) As of 2015, there were 256 reported cases of ECLS for near-fatal asthma (adults and children).…”
Section: Refractory Casesmentioning
confidence: 99%